1986
DOI: 10.1111/1365-3040.ep11611639
|View full text |Cite
|
Sign up to set email alerts
|

Water stress effects on guard cell anatomy and the mechanical advantage of the epidermal cells

Abstract: Vicia faba plants grown under water deficit were found to have guard cells considetably smaller than those of plants grown under well-watered conditions. Stomata of plants adapted to drought conditions have been observed in past studies to maintain opening at plant water potentials lower than those of plants not so adapted. By employing the geometric interpretation of the mechanical advantage (Wu, Sharpe & Spence, 1985), an anatotnical/mechanical basis was found that helps explain how sueh opening in drought c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…On stomata length, the result showed that IT and AR tend to have higher stomata length than CF. It probably indicated the adaptation of rice plant to water limited condition as reported by Spence et al (1986) and Kramer (1988). The present study showed that Si application clearly gave the positive effect on increasing stomata density on Ciherang variety throughout observation, which agreed with the previous results found in West Java (Siregar et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…On stomata length, the result showed that IT and AR tend to have higher stomata length than CF. It probably indicated the adaptation of rice plant to water limited condition as reported by Spence et al (1986) and Kramer (1988). The present study showed that Si application clearly gave the positive effect on increasing stomata density on Ciherang variety throughout observation, which agreed with the previous results found in West Java (Siregar et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Leaf size responded to salinity as expected: smaller leaves in higher salinities. Water deficit can affect leaf size by decreasing cell size and causing an increase in stomatal density (Quarrie & Jones, 1977;Spence, Wu, Sharpe, & Clark, 1986;Martínez, Silva, Ledent, & Pinto, 2007;Xu & Zhou, 2008). A study on L. racemosa and A. germinans did not show reductions of stomatal density with increases in salinity (Lovelock & Feller, 2003), which was confirmed by Schwarzbachl and Ricklefs (2001).…”
Section: Discussionmentioning
confidence: 69%
“…At the same time, it was determined that drought stress reduces the stomata sizes of maize plants, and gas exchange rates decreased in parallel with increasing drought stress [48]. A reduction of stomata sizes under salt stress protects the balance between photosynthesis and carbon intake, and prevents excessive water loss with transpiration [49]. These processes give the plant a xerophytic character [50] and help it to adapt to drought conditions caused by salt stress [51].…”
Section: Discussion Of Resultsmentioning
confidence: 99%